Diet and chronic constipation. Benefits of oral supplementation with symbiotic zir fos (Bifidobacterium longum W11 + FOS Actilight) - Amenta, M.; Cascio, M.T.; Di Fiore, et al., P. (Acta Biomedica Atenei Parmensis, 2006)
Background and aim: Constipation is one of the most common disorders in Western countries and it is known that dietary factors such as a low fiber diet and low caloric intake are associated with this condition. Weight loss can disrupt the intestinal ecosystem resulting in intestinal dysbiosis that worsens constipation. The aim of this study was to evaluate he effects of treatment with symbiotic zir fos (Bifidobacterium longum W11 + FOS Actilight) on chronic constipation in patients undergoing a weight loss diet. Methods: Our evaluation included the recording of age, gender, weight, height, BMI, physical activity, constipation, diet, therapy compliance and laxative supplies. A hypocaloric diet (1,200/1,400 cal.) was prescribed to all patients, and they were submitted to a physical activity program and received 1 bag of symbiotic zir fos per day for the entire duration of the study. Patients’ follow-up was available for up to 60 days. Results: Two hundred and ninety seven patients (79.4% women and 18.2% men, mean age 32.2) were included in the study. The mean baseline BMI was 33.4±5.6 (range 22.8-56.3 Kg). The improvement of constipation turned out to be associated to age (p